APPLICATION OF ATOMIC-FORCE MICROSCOPY TO STUDIES OF MICROBIAL INTERACTIONS WITH HYDROUS FE(III)-OXIDES - Maurice P.; Forsythe J.; Hersman L.; Sposito G. (My University, 1996)
We are using atomic-force microscopy (AFM), to address the interactions of a Pseudomonas sp. aerobic soil microbe with Fe(III)-(hydr)oxides. Research results to date show that AFM is a viable technique for in-situ and ex-situ imaging of bacteria attached to mineral surfaces. Delicate microbial structures and mineral surface microtopographies are readily accessible. However, sample preparation has proven to be crucial. For example, we found that an organic extractant used to separate bacteria from particle surfaces left a residue that could be mistaken for dissolution features in AFM images. Additionally, care must be taken to image samples in numerous locations and under a wide variety of conditions. The need for extensive imaging was reinforced by our observations that most reacted particles had no obvious dissolution features, but a small fraction of particles were extensively eroded. Hence, microbe-Fe(III)-(hydr)oxide interactions lead to enhanced dissolution, but the dissolution process is heterogeneous in nature. Thus, although AFM imaging of such complex systems is difficult and time-consuming, a painstaking approach is needed.